2015
DOI: 10.1021/acscombsci.5b00007
|View full text |Cite
|
Sign up to set email alerts
|

Solid-Phase Synthesis of Diverse Peptide Tertiary Amides By Reductive Amination

Abstract: The synthesis of libraries of conformationally-constrained peptide-like oligomers is an important goal in combinatorial chemistry. In this regard an attractive building block is the N-alkylated peptide, also known as peptide tertiary amide (PTA). PTAs are strongly biased conformationally due to allylic 1,3 strain interactions. We report here an improved synthesis of these species on solid supports through the use of reductive amination chemistry using amino acid-terminated, bead-displayed oligomers and diverse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
41
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 40 publications
(41 citation statements)
references
References 20 publications
0
41
0
Order By: Relevance
“…Formation of urea linkages following nucleophilic addition to an isocyanate proceeds with high yield and 61% DNA remaining. Reductive amination 39 of an aldehyde with a resin-bound amine proved to be an ideal reaction, proceeding with 90% yield and no detectable loss in DNA amplifiability. Suzuki-Miyaura cross-coupling, 40 a carbon-carbon bond forming reaction of a boronic acid and resin-bound aryl iodide, was optimized to 93% yield of biphenyl product and 47% DNA remaining.…”
Section: Resultsmentioning
confidence: 99%
“…Formation of urea linkages following nucleophilic addition to an isocyanate proceeds with high yield and 61% DNA remaining. Reductive amination 39 of an aldehyde with a resin-bound amine proved to be an ideal reaction, proceeding with 90% yield and no detectable loss in DNA amplifiability. Suzuki-Miyaura cross-coupling, 40 a carbon-carbon bond forming reaction of a boronic acid and resin-bound aryl iodide, was optimized to 93% yield of biphenyl product and 47% DNA remaining.…”
Section: Resultsmentioning
confidence: 99%
“…14A). It is possible to include N-alkylated derivatives of many different amino acids into a library 102 , but in this case, the N-alkylated amino acid (where the side chain is larger than methyl) must be followed by a peptoid unit since chloroacetyl chloride is the only acylating agent that couples in high enough yield to the sterically congested amine to support the synthesis of high-quality libraries 32 .…”
Section: Libraries Of Conformationally-restricted Oligomers: Ptas Andmentioning
confidence: 99%
“…Therefore, in the future it will be important to develop new library designs of different types of molecules that can be made with gentler reactions. For example, we have found that reductive amination 102 is a “freebie” with little or no damage to the DNA. We are working on adapting to the solid phase various reactions that are efficient in solution under conditions that are not DNA damaging.…”
Section: Dna-encoded Oboc Librariesmentioning
confidence: 99%
“…One of the simplest examples of this approach is the construction of libraries of peptide tertiary amides (PTAs), in other words, oligomers of N -alkylated amino acids 110,111,114 (Fig. 11).…”
Section: Introductionmentioning
confidence: 99%